(untitled) (Heritage, 2020)
In thepaper the assessment of the Debar direction by a commission determined to establish the border towards Albania is analyzed. The characteristics of the terrain are listed, as well as the possibilities for adequate blocking, primarily for the purpose of protection against armored units. The source of the work was the reports of the commissions, as well as the memories of the individuals involved in the evaluation and, later, in the work performance.